Hyperhomocyst(e)inemia and endothelial dysfunction in IDDM - Hofmann Bowman, Marion; Kohl, Brigitte; Klevesath, Martina; Borcea, Valentin; Bierhaus, Angelika; Henkels, Mechthild; Amiral, Jean; Schmidt, Ann Marie; Fiehn, Walter; Ziegler, Reinhard; Wahl, Peter; Nawroth, Peter Paul (Diabetes care, 1998)
Considering that elevated blood levels of homocyst(e)ine represent a known independent risk factor for macrovascular disease, we assessed the link between hyperhomocyst(e)inemia and diabetic microvascular complications.Homocyst(e)ine and thrombomodulin plasma levels, a marker of endothelial cell damage, were measured before and 3 h after oral methionine loading in 75 patients with stable, well-controlled IDDM and 40 healthy control subjects matched for sex and age. Exclusion criteria were hyperlipidemia, hypertension, smoking, or positive family history for cardiovascular disease.IDDM patients had higher pre- and postload homocyst(e)ine plasma levels than did healthy control subjects (12.0 vs. 7.7 umol/1 and 27.6 vs. 16.0 umol/1; P < 0.001). Of 75 IDDM patients, 26 had homocyst(e)ine plasma levels above the normal range (defined as mean ± 2 SD of values obtained in the control group). The IDDM patients with hyperhomocyst(e)inemia had higher thrombomodulin plasma levels (62.2 vs. 38.2 ng/ml; P < 0.001), higher albumin excretion rates (485 vs. 115 mg/1; P < 0.005), and a higher prevalence of late diabetic complications (nephropathy 76 vs. 33%; retinopathy 69 vs. 51%; neuropathy, 57 vs. 41%; macroangiopathy 57 vs. 33%) compared with IDDM patients with normal plasma homocyst(e)ine. In vitro experiments with human umbilical vein cells show an increased release of thrombomodulin into the culture supernatant only when endothelial cells were pretreated with advanced glycation end product (AGE)-albumin before L-homocystine was added. A synergistic action of homocyst(e)ine and AGEs might contribute to vascular complications of patients with diabetes.Hyperhomocyst(e)inemia is common in nephropathic diabetic patients and may contribute to the enhanced morbidity and mortality from cardiovascular diseases characteristically observed in IDDM patients with diabetic nephropathy.